Implementation of Problem Based Learning to Improve Students' Learning Independence in Islamic Education Learning at SD Negeri 101931 Perbaungan - Hutabarat, Herlina; Fadhilah; Masitah (Jurnal Pendidikan Profesi Guru, 2024)
This study aims to improve students' learning independence in Islamic religious education learning by using Problem Based Learning. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Learning through Problem Based Learning can improve students' learning independence in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, Learning through Problem Based Learning can be used as an alternative to improve students' learning independence in Islamic religious education learning